2012
DOI: 10.3109/0167482x.2012.656161
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and experiences of women who accessed “see and treat” cervical cancer prevention services in Zambia

Abstract: Background In Zambia, a country with a generalized HIV epidemic, age-adjusted cervical cancer incidence is among the highest worldwide. In 2006, the UAB-Center for Infectious Disease Research in Zambia and the Zambian Ministry of Health launched a visual inspection with acetic acid (VIA)-based “see and treat” cervical cancer prevention program in Lusaka. All services were integrated within existing government-operated primary health care facilities. Objective Study aims were to: 1) identify women's motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Promiscuity, unsanitary life style and evil curses were seen as some of the reasons a woman will be hesitant going for cervical screening (White et al . ). Participants in these studies also reported their fear of societal rejection as a reason affecting disclosure of early symptoms and utilisation of cervical cancer screening services.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Promiscuity, unsanitary life style and evil curses were seen as some of the reasons a woman will be hesitant going for cervical screening (White et al . ). Participants in these studies also reported their fear of societal rejection as a reason affecting disclosure of early symptoms and utilisation of cervical cancer screening services.…”
Section: Resultsmentioning
confidence: 97%
“…White et al . () revealed that the gender of the care giver can be a hindrance to screening. The authors further revealed that having to undress for the procedure was a major barrier to utilisation.…”
Section: Resultsmentioning
confidence: 99%
“…A Medline literature search found only 2 studies in Africa on the motivations of women who underwent VIA screening, and both were carried out in Zambia in southern Africa [10,11]. The aim of the present study was therefore to evaluate the motivations and preferences of southeastern Nigerian women who underwent VIA.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Located in the outskirt of Lusaka, this government-run health center provides a wide range of preventive and curative services to the surrounding community, including cervical cancer preventive care, and HIV, maternal and child care. Cervical cancer screening is currently available every week day, free of charge.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 We also conducted extensive field testing in local languages to ensure that choice questions were relevant and understood by the respondents. Because the study included low-literacy women, the number of attributes was limited to five and the maximum number of attribute options to four.…”
Section: Methodsmentioning
confidence: 99%